(3GdZQI GdefjaI aj JQLjM ePgH GdEeGe CHj MfjaIs - (3YeQ Hf ESMGb Hf CMeO GdgfOj GdZRfhj, SQGL GdOjf, CHh MaU,J (B773 (3g` s
(3ChdgG (B:s
(3GdMeO ddg Ydi GdBFg hHYO , abO GTGQ Edi GdCejQ GdcHjQ UjQ ZJeS Gdedci GdfGUQi Cf CJQLe HGdYQHjI cJGH GdWQjbI GdHgGFjI s
(3BNQgG (B:s
(3hgPg bWQI ef HMGQ GdeSGFd GdJi jMJGL GdfG Edi JbdjO GdEeGe CHj Mfjag QVi Gddg Yfg ajgG hGddg CYde s
(3GdfSNI efbhdI ef fSNI fbdJ ef fSNI HNW GdeUfa LGA ajgG Efg aQZ ef JCdjag SfI (B759s
(3HgG fXGe GdJYbjHIs
(3gPG GdcJGH JQLeI dcJGH GdWQjbI GdHgGFjI GdJi Ufag GdEeGe aNQ GdOjf GdQGRi ddSdWGf GdeQMhe HgGA GdOjf HGdaGQSjI hRjGOI Ydjg OdGFd hCLhHI ef LGf s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B42 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B276s
(3JHUQGJ GdCUd (B:s
Keywords: (3Gdabg GdMfajs